Bone Morphogenetic Proteins Shape Treg Cells - Kraj, Piotr (Frontiers in Immunology, 2022)
The transforming growth factor-β (TGF-β) family includes cytokines controlling cell behavior, differentiation and homeostasis of various tissues including components of the immune system. Despite well recognized importance of TGF-β in controlling T cell functions, the immunomodulatory roles of many other members of the TGF-β cytokine family, especially bone morphogenetic proteins (BMPs), start to emerge. Bone Morphogenic Protein Receptor 1α (BMPR1α) is upregulated by activated effector and Foxp3+ regulatory CD4+ T cells (Treg cells) and modulates functions of both of these cell types. BMPR1α inhibits generation of proinflammatory Th17 cells and sustains peripheral Treg cells. This finding underscores the importance of the BMPs in controlling Treg cell plasticity and transition between Treg and Th cells. BMPR1α deficiency in in vitro induced and peripheral Treg cells led to upregulation of Kdm6b (Jmjd3) demethylase, an antagonist of polycomb repressive complex 2 (PRC2), and cell cycle inhibitor Cdkn1a (p21Cip1) promoting cell senescence. This indicates that BMPs and BMPR1α may represent regulatory modules shaping epigenetic landscape and controlling proinflammatory reprogramming of Th and Treg cells. Revealing functions of other BMP receptors and their crosstalk with receptors for TGF-β will contribute to our understanding of peripheral immunoregulation.